2018
DOI: 10.1017/s0959270918000151
|View full text |Cite
|
Sign up to set email alerts
|

Use of semi-intensive shrimp farms as alternative foraging areas by migratory shorebird populations in tropical areas

Abstract: SummaryEvaluating the ability of anthropogenic habitats to serve as surrogates for natural habitats is an increasingly relevant issue in conservation biology. This issue is especially urgent in tropical coastal wetlands that support large concentrations of migratory shorebird populations and are under pressure from development. Here we evaluated the species composition, abundance, and habitat use of Nearctic migratory shorebirds using recently harvested aquaculture ponds during two non-breeding seasons at shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In many areas of South America, changes to shorebird habitats in coastal areas are a direct result of human activities, and in northeast Brazil the main impacts are related to the conversion of mangroves and associated habitats into salinas and shrimp farms (Ferreira & Lacerda, 2016; Valenti et al, 2021). Although some previous studies have suggested that shrimp farms can be important to shorebirds and other waders (Basso et al, 2018; Masero, 2003; Navedo & Fernández, 2019), such heavily altered habitats, including both shrimp farms and salinas , may also present a greater overall risk via general habitat reduction, exposure to predators such as feral cats, environmental degradation and exposure to contaminants like heavy metals during non‐breeding periods (Burger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many areas of South America, changes to shorebird habitats in coastal areas are a direct result of human activities, and in northeast Brazil the main impacts are related to the conversion of mangroves and associated habitats into salinas and shrimp farms (Ferreira & Lacerda, 2016; Valenti et al, 2021). Although some previous studies have suggested that shrimp farms can be important to shorebirds and other waders (Basso et al, 2018; Masero, 2003; Navedo & Fernández, 2019), such heavily altered habitats, including both shrimp farms and salinas , may also present a greater overall risk via general habitat reduction, exposure to predators such as feral cats, environmental degradation and exposure to contaminants like heavy metals during non‐breeding periods (Burger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates suggest that 20,000–30,000 ha of coastal habitat was being used for shrimp production in 2020 (Lacerda et al, 2021). While shrimp farms have provided alternative foraging habitats for shorebirds in some cases (Basso et al, 2018; Navedo et al, 2015; Navedo & Fernández, 2019), the actual importance and potential impacts of these highly modified habitats for shorebirds in other locations is relatively unknown (Burger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the face of large-scale loss of natural habitat (Newbold et al, 2015;Diaz et al, 2019), expanding artificial landscapes, such as farmlands, commercial saltpans, and plantations, sometimes provide alternative habitat for wildlife (Ma et al, 2010;Katayama et al, 2019). Understanding the role of artificial habitats in wildlife population maintenance has become essential for biodiversity conservation (Navedo & Fernández, 2019;Wang et al, 2022). The global aquaculture industry has expanded rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In northwestern Mexico, semi‐intensive shrimp farms (following Edwards, 1993 ) enmeshed within surrounding coastal wetlands are widely used by shorebirds to forage throughout the shrimp‐harvesting period between October and December (Navedo & Fernández, 2019 ; Navedo et al., 2015 ). These anthropogenic habitats represent ideal arenas to study trade‐offs between starvation and predation risk from a complete ecological perspective for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…These anthropogenic habitats represent ideal arenas to study trade‐offs between starvation and predation risk from a complete ecological perspective for a number of reasons. First, high densities of Nearctic shorebirds forage at recently harvested ponds, even at those shrimp farms adjacent to or embedded with large coastal wetlands (Navedo & Fernández, 2019 ). Second, predators as peregrine falcons ( Falco peregrinus ) are often observed hunting on shorebirds at shrimp farms (Basso et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%